2023
DOI: 10.3390/buildings13112787
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Compressive Strength in Cementitious Composites through Effective Use of Wasted Oyster Shells and Admixtures

Inyeong Cha,
Jinwoong Kim,
Heeyoung Lee

Abstract: Wasted oyster shells generate environmental pollution and odor, thereby causing inconvenience to people. In addition, low-quality aggregates are generated owing to the lack of sand. To address these problems, cementitious composites that replaced sand with oyster shell powder were fabricated in this study, and a total 120 specimens were fabricated (specimen size: 50×50×50 mm3). The oyster shell substitution rate for sand, admixture type, and presence or absence of admixture were set as the experimental paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…That is, an excessively high inclusion of WOSP can disrupt its intended role, leading to a reduction in strength. The absence of WOSP leads to denser microstructures, which is in line with previous findings [62,63]. Overall, it can be concluded that a high WOSP replacement ratio can negatively influence strength development owing to reduced reactivity.…”
Section: Effect Of Wosp Replacement Ratio On the Strength And Microst...supporting
confidence: 91%
“…That is, an excessively high inclusion of WOSP can disrupt its intended role, leading to a reduction in strength. The absence of WOSP leads to denser microstructures, which is in line with previous findings [62,63]. Overall, it can be concluded that a high WOSP replacement ratio can negatively influence strength development owing to reduced reactivity.…”
Section: Effect Of Wosp Replacement Ratio On the Strength And Microst...supporting
confidence: 91%